BALANCING BELIEF AND PRACTICE: RELIGIOUS HOSPITALS IN AN EVOLVING MEDICAL LANDSCAPE - Miller, Lauren E (International Journal of Contemporary Health Sciences and Technology, 2025)
In 2021, health expenditures in the United States soared to $4.3 trillion, constituting 18.3% of the Gross Domestic Product (GDP). Within these expenditures, hospital inpatient services accounted for 19% of total healthcare costs, making it a significant component. This paper delves into the challenges faced by religious hospitals, which often serve as safety net providers and grapple with the complexities of delivering charity care. In response, these hospitals must enhance operational efficiency and foster coordinated care between inpatient and outpatient facilities. Moreover, the financial landscape for religious hospitals is further complicated as government funding, particularly from Medicare and Medicaid, becomes increasingly constrained. The introduction of the CMS withhold rate for Value-Based Purchasing in 2017 led to a 2% reduction in hospitals' base payments, amounting to $1.8 billion withheld, with these funds being redirected to hospitals with superior quality scores. To remain competitive in the evolving healthcare market, religious hospitals must adapt and improve their operations.